Holoceńskie okresy intensyfikacji procesów stokowych w Gorcach – porównanie najnowszych wyników badań = Periods of intensified hillslope processes in Poland’s Gorce Mountains during the Holocene – a comparison based on new data - Kroh, Paweł. Autor; Okupny, Daniel. Autor; Bryndal, Tomasz. Autor; Kondracka, Marta. Autor; Cybul, Piotr. Autor (IGiPZ PAN, 2021)
This paper presents selected results from efforts to date organic matter taken from deposits of three landslides in Poland’s Gorce Mts. i.e. the ones located below the Jaworzyna Kamienicka, Kudłoń and Góra Gębowa peaks. The material for dating was taken from two landslide peat bogs and one closed depression filled with mineral deposits. The ranges of the individual landslides were analysed by reference to a detailed terrain model as well as geophysical tests, while the organic samples collected were 14C radiocarbon-dated. The borehole drilled in the landslide below Jaworzyna Kamienicka reaches a depth of 2.2 m. It was from that profile that samples for 14C radiocarbon-dating, as well as palaeobotanical and geochemical study, were taken. The oldest deposits on the floor part of the peatland were dated to 8060±100 BP (8949 cal BP). The first level of gravels mixed with so-called organic chaff was dated to 7950±80 BP (8802 cal BP) and is deposited directly beneath a layer of peats dated to 75600±100 BP (8366 cal BP). Another important layer is of gravel and fragments of wood, 9 cm thick, deposited at a level dated to 3999±60 BP (4517 cal BP). Three boreholes were drilled in the peat bog below Kudłoń, with the oldest peat deposits at this site are dated to 5430±70 BP (6002 cal BP), and situated at a depth of 100‑80 cm. In the other two places deposits in the floor profile were dated to 3010±60 BP and 400±60 BP. No mineral levels nor levels with a high share of mineral parts were found. Into the landslide below Góra Gębowa eight boreholes were made within a closed depression filled with mineral deposits. A fragment of wood taken from borehole 5 at a depth of 2.2 m was dated to 8850±100 BP (9739 cal BP), while one from a depth of 1 m is associated with a date of 8070±100 BP (8959 cal BP). In turn, the floor of borehole 6, at a depth of 2.1 m was the source for a wood sample of determined age equal to 8440±110 BP (9329 cal BP). The oldest deposits in the Gorce Mts. are of a fen character and area aged 9500 ± 90 BP (11 143‑10 653 cal BP). They come from the Turbacz Range. The next landslide phase is confirmed by wood fragments from the landslide below Góra Gębowa (8850±100 BP, 9739 cal BP), and could also be linked with rise of C. avellana within forest structure, as well as with the period of intense mineral-material deposition reported from four places in Makowski Beskid Mts. A following phase of landslide formation is confirmed by data from Jaworzyna Kamienicka (8060±100 BP, 8949 cal BP) and Lake Zawadowskie (7947‑7685 cal BP, Buczek, 2019), and represents the effect of the increased humidity and cooling of the climate reported from the Western Carpathians by many researchers. The oldest deposits from the peat bog below Kudłoń date to 5430±70 BP (6002 cal BP). Such a result is consistent with the increase in organic matter in Lake Zawadowskie in this period (5420± 60 BP). The traces from that period recorded by Buczek (2019), and the dating of deposits beneath Kudłoń, may both indicate that a period 6.0‑5.5 ka cal BP was the next one in which morphogenetic activity in the Gorce Mts. increased. The formation of the Lelonek landslide (401 ±70 BP) could be treated as evidence of a next landslide-creation phase (Buczek, 2019) also gaining confirmation from Margielewski (2018). There is also a gravel-wood level in the core from Jaworzyna Kamiecka dated at 3999±60 BP; 4517 cal BP. Kołaczek et al. (2020) noted a major change of forest structure with increases of A. alba, F. sylvatica and C. betulus at ~4.0 ka BP (~4.5 ka cal BP). This attests to the period in question being one characterized by a high level of landslide activity. Comparison of all the latest data from the region in question sustains the conclusion that ~11.1 ka cal BP, ~9.7 cal BP, 8.6‑8.0 cal BP, ~6,0 cal BP and ~4.5 ka cal BP, 3.3‑2.5 cal BP and 1.75‑1.35 cal BP are all periods associated with intensified Holocene landslide movements in the Gorce Mountains.
24 cm
Keywords: radiocarbon dating; landslide fen; mineral and biogenic deposits; mass movement activity; Holocene; Flysch Carpathians